An improved mapping pattern for digital watermarking - Mohamad Nazmi, Nasir (2019)
In the present, watermark plays an important part in all copyrighted content whether it is physical or digital. The importance of watermark in digital data increases as the usage of internet in transferring data increases day by the as the improvement in technologies improves. Therefore, the term digital watermark become more and more famous as we become more dependent on digital information. Digital watermarking can be used on RGB images to protect the ownership of the images. An image consists of many pixels and the digital watermark uses the Least Significant Bit (LSB) to apply the watermark. This is to reduce the disturbance to the original image as much as possible as it might alter the colour of the original image. The digital watermark is located in the LSB because the human eye has a limit on seeing the fewest disturbance that has been made on the original image. The fewer the disturbance on the original image, the better the digital watermark as the main objective of using digital watermark is to apply the highest security as possible to the digital image and in the same time to reduce as most disturbance as possible that can be visible to the human eye. This research proposed a hybrid mapping pattern which is Hilbert Peano Curve to try to achieve the highest security as possible from alteration. The result of the experiments will be compared with the existing watermark to prove the security of the proposed pattern. The results of this research are expected to be better in terms of security if compared to other digital watermarking schemes.